Integrative Analysis of Physiological Phenotype of Plant Cells by Turgor Measurement and Metabolomics - Yousef Gholipour (2012)
Water status and metabolite content are considered as two key features in plant cell physiological phenotype. In order to profiling "in situ" living plant cell status, turgor pressure of cells located at different locations of tissues was probed with a cell pressure probe and then cell sap was sampled and its metabolite profile was generated with using nanoESI and MALDI mass spectrometry. No purification or separation was included in workflow and picoliter cell sap samples were injected directly into a nanoESI-Orbitrap mass spectrometer and/or deposited on selected matrices from organic compounds and nanoparticles for MALDI-TOF mass spectrometry analysis. Both shotgun mass spectrometry techniques could be used for detecting and quantifying metabolites in single-cell samples. Different metabolites from neutral carbohydrates to amino acids and secondary metabolites could be detected. Quantity of two major metabolites, sucrose and kestose, was also measured in several cells and sucrose concentration was co-plotted with turgor data.